Improving Fiqh Learning Outcomes Through the Application of Learning Methods for The Demonstration of Plural Prayers, Qasar, Plural Qasar, and Prayers in Emergency Situations for Students in Class VII-3 MTSN 2 Kendari - Nusriati (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2021)
The purpose of this study was to determine the increase in student activity and learning outcomes through the application of the Demonstration Method learning model. This type of research is the PTK, in which each cycle consists of the stages of planning, action, observation, and reflection. The results showed that there was an increase in student activity and learning outcomes in each cycle. This is shown in pre-cycle conditions, the percentage of student learning outcomes is only around 36.84%, cycle I (73.68%), and cycle II has reached a percentage of learning completeness of around 92.11% and it can be stated that in cycles I and II, completeness of student learning outcomes has reached indicators of success (73%). Then the results of the increase in student learning activeness also appear to have increased, marked by the results obtained at the pre-cycle stage only reached 50%, cycle I (76.92%), and in the second cycle stage had reached an active value of around 90.38% so that it could be stated that learning activeness has met the success indicator (70%) in cycles I and II. Therefore, the use of the Learning Model using the Demonstration Method can improve student activity and learning outcomes in the Fiqh Subject for the material of the Plural, Qashar, Plural Qashar, and prayer in an Emergency in Class VII-3 MTsN 2 Kendari.